Contextualizing Sambisari Temple as a Learning Resource: Integrating Multicultural Values in High School History Education - Ponco Setiyonugroho; Arief Hidayat; Yusuf Budi Prasetya Santosa (Fajar Historia: Jurnal Ilmu Sejarah dan Pendidikan, 2026)
The cultivation of multicultural values in education has become an urgent necessity amid the increasing diversity of contemporary society. History education holds a strategic role in fostering awareness of cultural, religious, and social diversity within Indonesian society. This article aims to examine how the integration of multicultural values can be implemented through the utilization of local cultural heritage sites, particularly Sambisari Temple, as a contextual learning resource in history education. Employing a literature review approach, this study explores the symbolic, historical, and educational potential of Sambisari Temple as a medium for multicultural value learning. The findings indicate that Sambisari Temple is not only an archaeological legacy of the Ancient Mataram Hindu civilization but also a concrete representation of a social life characterized by tolerance and openness to differences. Through the exploration of the values of diversity embedded in the site, such as architectural diversity, socio-religious functions, and the heterogeneous surrounding community history, teachers can develop contextual learning models that foster empathy, tolerance, and inclusive attitudes among students. Integrating Sambisari Temple into history learning also supports the strengthening of the Pancasila Student Profile, particularly in the aspects of critical reasoning and global diversity awareness. This article recommends the development of culturally site–based instructional materials as well as teacher training programs to maximize the potential of multicultural education in history classrooms through a locality-based approach. These findings are relevant in addressing the challenges of 21st-century education in shaping citizens who possess historical awareness and multicultural character.